2000
DOI: 10.1046/j.1365-2567.2000.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

The lipid A region of lipopolysaccharides from Rhizobiaceae activates bone marrow granulocytes from lipopolysaccharide‐hyporesponsive C3H/HeJ andC57BL/10ScCr mice

Abstract: SUMMARYWe established in previous studies that the binding of Salmonella lipopolysaccharide (LPS) to constitutive receptors of low af®nity triggers the expression of the inducible LPS-binding molecule CD14 in bone marrow cells (BMC) of C3H/HeOU mice, but not in BMC from C3H/HeJ mice. We show in this study that BMC from C3H/HeJ and C57BL/10ScCr mice do not express CD14 after exposure to LPSs from Salmonella enterica and Bordetella pertussis, but do express this marker when treated with several LPSs from Rhizobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…This is particularly the case with the LPSs from Pseudomonas aeruginosa (Pier et al, 1981), Porphyromonas gingivalis (Tanamoto et al, 1997;Ogawa et al, 1996) and Prevotella intermedia (Kirikae et al, 1999). In a recent study (Pedron et al, 2000), we found that LPSs from Rhizobiaceae and their structurally atypical lipid A moieties can stimulate BMGs from TLR4-deficient mice (C3H/HeJ and C57BL/10 ScCr) and induce the expression of CD14 in these cells.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…This is particularly the case with the LPSs from Pseudomonas aeruginosa (Pier et al, 1981), Porphyromonas gingivalis (Tanamoto et al, 1997;Ogawa et al, 1996) and Prevotella intermedia (Kirikae et al, 1999). In a recent study (Pedron et al, 2000), we found that LPSs from Rhizobiaceae and their structurally atypical lipid A moieties can stimulate BMGs from TLR4-deficient mice (C3H/HeJ and C57BL/10 ScCr) and induce the expression of CD14 in these cells.…”
mentioning
confidence: 90%
“…We established in a previous study (Pedron et al, 2000) that the lipid A region of several LPSs from Rhizobiaceae can stimulate BMGs of the TLR4-deficient mouse strains C3H/HeJ and C57BL/10ScCr, and induce the expression of CD14 in these cells. This suggests that LPSs from Rhizobiaceae are recognized by another member of the Toll family, or by another receptor.…”
Section: Tlr2-mediated Expression Of Cd14 Induced By the Lipid A Of Rmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20,43,44 However, TLR2 can only recruit the adaptor protein MyD88 and as a result can only initiate the production of MyD88-dependent cytokines such as TNF-α, but not those TRIF-dependent cytokines such as IFN-β. 3,4 The fact that our results show that R. sin-1 can induce the production of IFN-β prompted us to investigate the TLR utilization of these compounds.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…17,18 Furthermore, another study showed that the biological properties of R. sin-1 LPS are species specific and most notably it was found that it can agonize mouse macrophages in a TLR2-dependent manner. 19,20 The lipid A of R. sin-1 LPS is structurally unusual lipid A differing in almost every aspect from those known to contribute to the toxicity of enteric LPS (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%